2010
DOI: 10.1175/2010jamc2133.1
|View full text |Cite
|
Sign up to set email alerts
|

Improved Estimates of the European Winter Windstorm Climate and the Risk of Reinsurance Loss Using Climate Model Data

Abstract: Current estimates of the European windstorm climate and their associated losses are often hampered by either relatively short, coarse resolution or inhomogeneous datasets. This study tries to overcome some of these shortcomings by estimating the European windstorm climate using dynamical seasonal-to-decadal (s2d) climate forecasts from the European Centre for Medium-Range Weather Forecasts (ECMWF). The current s2d models have limited predictive skill of European storminess, making the ensemble forecasts ergodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…Fourth, there is also considerable statistical uncertainty obvious from the relatively wide confidence intervals of the GPD fit estimates, in particular for long return periods above approximately 25 years. Reducing this uncertainty requires larger samples of storm loss data by including longer datasets of wind speed, for example, or by using ensemble simulations (Della-Marta et al, 2010;Donat et al, 2010b).…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
“…Fourth, there is also considerable statistical uncertainty obvious from the relatively wide confidence intervals of the GPD fit estimates, in particular for long return periods above approximately 25 years. Reducing this uncertainty requires larger samples of storm loss data by including longer datasets of wind speed, for example, or by using ensemble simulations (Della-Marta et al, 2010;Donat et al, 2010b).…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
“…Della-Marta et al (2010) found that estimation using L-moments resulted in lower biases in parameter estimates for small sample sizes than using maximum likelihood estimates. Figure 5 shows the return period of modelled loss for the historical and 22 RCM storm sets.…”
Section: The Rcm Storm Sets and Their Damagesmentioning
confidence: 94%
“…An alternative method of calibration that permits the possibility of higher wind speeds than has been observed in history would be to fit extreme value distributions to the highest wind speeds in the RCM and historical storm sets and then quantile match the wind speeds with reference to these distributions. Della-Marta et al (2010) used such an approach to calibrate indices of storms between two models. It would be worth considering here, but the geographically-dependent calibration used here would require a robust automatic threshold detection algorithm for peak-over-threshold extreme value distributions.…”
Section: The Rcm Storm Sets and Their Damagesmentioning
confidence: 99%
“…Wind storm occurrence has particularly high variability (Bärring and von Storch, 2004;Wang et al, 2009). Hence, a reliable estimation of long-term changes requires large samples, which can also be obtained from ensemble simulations (see, for example, Della-Marta et al, 2010;Donat et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%